(untitled) (Society of Pharmaceutical Scienc, 2022)
The extraction condition, physic-chemistry characterization, and antioxidant activity of pectin from cactus Opuntia dillenii found commonly growing in the Ninh Thuan coast, Vietnam, were studied. The extraction conditions of antioxidant pectin content, such as temperature, time, cactus-to-solvent ratio, solvent pH, and extraction numbers, were surveyed. A correlation between pectin content and antioxidant activities, physic-chemistry characterization such as FTIR spectra, sugar composition, viscosity, solubility ability, and esterification degree of antioxidant pectin were also analyzed. The results showed that the extraction condition strongly affected (p < 0.05) and close correlation (R2 > 0.9) on pectin content and antioxidant activities. The pectin content and the antioxidant activities got the highest value at the condition (pH 4, the solvent/material of 6/1 (v/w), the extracting time of 90 min, and extracting temperature of 90 ºC). Glucuronic and galacturonic acid of antioxidant pectin occurred from 20.920 min to 21.765 min and 20.915 min to 21.779 min, respectively. Pectin possessed an esterification degree of 62.38 ± 0.94 %, viscosity of 0.893 ± 0.051 Pa.s, and fully solubility in 90 ºC. They fully dispersed into hot water and formed gelation in cold water. Antioxidant pectin of cactus Opuntia dillenii grown in the Ninh Thuan coast is useful for application into the foods industry.